Knowledge and attitudes about the use of emergency contraception among college students in Tamil Nadu, India - Davis, Prem (J Egypt Public Health Assoc, 2020)
BACKGROUND: In India, a large number of pregnancies are unplanned resulting in unsafe and illegal abortion. For every legal abortion, 10 to 11 illegal abortions are occurring which endangers the health and survival of the women. In recent years, there is an increase in unwanted and unintended pregnancy at the early age group. Usage of emergency contraception (EC) can decrease the unwanted pregnancy and provide a healthier life. AIM: The aim of study is to assess the knowledge and attitude regarding EC among college students in Thiruvarur District, Tamil Nadu, India. METHODS: A cross-sectional study was conducted among the college students of Thiruvarur district, Tamil Nadu, India. A total of 758 students were selected by convenient sampling technique. Data was collected by administering a pretested semi-structured questionnaire. RESULTS: Out of 758 students, 183(24%) heard about EC. The commonest source of information was the internet 91 (49.7%). The majority 116 (63.4%) knew that it does not prevent STDs. Of those who were aware, 42% were aware of 42.6% are aware of the time limit to use EC. The knowledge level of about the EC was moderate (60.1%), and it was significantly (p < 0.05) more among students > 25 years old, married participants, students in private institution, of lower socio-economic status, Muslim students and days’ scholars. The negative attitude towards EC was 59%. Nearly 38.8% believed that the EC will affect the next menstrual period, and 35.5% informed it will increase high risk behaviour among adults. The attitude level was significantly associated with the same factors associated with the awareness level with the factors Christian religion replacing Muslim and higher socioeconomic class replacing lower class participants. CONCLUSION: The knowledge level of the studied college students was moderate, and they mostly had negative attitude towards the EC. Reproductive health education should be given in educational institutions to promote awareness and to remove misconceptions about EC.